A Mendelian Randomization Analysis to Expose the Causal Effect of IL-18 on Osteoporosis Based on Genome-Wide Association Study Data - Kou, Ni; Zhou, Wenyang; He, Yuzhu; Ying, Xiaoxia; Chai, Songling; Fei, Tao; Fu, Wenqi; Huang, Jiaqian; Liu, Huiying (Frontiers in Bioengineering and Biotechnology, 2020)
Accumulating evidence showed that Interleukin (IL) level is associated with Osteoporosis. Whereas, most of these associations are based on observational studies. Thus, their causality was still unclear. Mendelian randomization (MR) is a widely used statistical framework that uses genetic instrumental variables (IVs) to explore the causality of intermediate phenotype with disease. To classify their causality, we conducted a MR analysis to investigate the effect of IL-18 on the risk of Osteoporosis. First, based on summarized genome-wide association study (GWAS) data, 8 independent IL-18 SNPs reaching genome-wide significance were deemed as IVs. Next, Simple median method was used to calculate the pooled odds ratio (OR) of these 8 SNPs for the assessment of IL-8 on the risk of Osteoporosis. Then, MR-Egger regression was utilized to detect potential bias due to the horizontal pleiotropy of these IVs. As a result of simple median method, we get the SE (-0.001; 95% CI -0.002 to 0; P = 0.042), which means low IL-18 level could increase the risk of the development of Osteoporosis. The low intercept (0; 95% CI -0.001 to 0; P = 0.59) shows there is no bias due to the horizontal pleiotropy of the IVs.